Development and evaluation of a screening test kit for detection of tetracycline group residues in honey - Chuleeporn Saksangawong (2018)
Extensive use of antibiotics in bee colonies can cause an accumulation of residues in honey and become a public health hazard. Analysis of antibiotic residues, therefore, is essential for consumer protection purposes. This study developed and evaluated a simple, rapid, and inexpensive screening test kit for detecting tetracycline group residues in honey. A microbial inhibition assay was carried out using spores of Geobacillus stearothermophilus (DMST 8041) in optimal medium with bromocresol purple as an indicator. Prepared 0.1 ml of 30% honey solution was incubated at 65 ± 1°C for 2-3 hours in a water bath. A positive reaction was detected by negligible change of the purple medium, indicating the presence of a substance(s) that can prevent the growth of the test organism. A negative reaction, indicating an absence of antibiotic residue in sufficient quantity to inhibit bacterial growth, showed a complete change of the medium's color, due to bacterial propagation, from purple to yellow. Using negative and positive controls (honey free of any residues and honey spiked with varying concentrations of residue, respectively), the screening test kit was 99% accurate. The test kit had a detection limit for tetracycline group residues in honey of 10 μg/kg. The shelf life of the test kit kept refrigerated at 4-8°C was 9 months. The test kit was then used to test 120 commercially available honey samples from across northern Thailand for tetracycline group residues. All 120 samples tested free of antibiotic residues using the new test kit. Of these samples, 30 were randomly selected and subjected to antibiotic residue test using HPLC technique to validate the results from the new screening test kit. Only one of the samples tested positive (8.85 μg/kg of chlortetracycline) at a concentration below the 10 μg/kg detection limit of the test kit.